(untitled) (Journal of Applied Learning and Teaching, 2022)
Mobile-assisted language learning (MALL) was first introduced in 1993 and became a sub-area of the growing field of mobile learning research. It has inspired learners to make use of the “anytime” and “anywhere” technology, the key concepts in MALL. Though some mobile apps for Mandarin learning are available, many challenges of the current MALL technology have been recognized. In order to tackle these challenges, we (author and her colleague in Computer Science Department) have designed a mobile app (Android and iOS) as a Mandarin supplementary learning tool, using micro-learning theory. Learning content can be easily customized as needed according to the textbook, which allows both seamless alignments with college curriculum and more quantitative study of MALL technology, with a large group of students over a long period. In addition, the data of students’ behaviours and performances, including how often the student used it and what the results are, can be traced. The analysis of these data allows the use of micro-learning for both students and instructors, which facilitates the language learning. We will pilot the app and conduct various experiments in multiple sections of Chinese I in our college to assess the effectiveness of the proposed app for free. The app can be also applied to other foreign languages with little effort.